Strength and Creep of Frozen Ground - Voitkovskii,K. F. (1970)
The book presents results of experimental and theoretical investigations on the strength and creep of frozen ground, summing up modern views of the rheology of frozen ground. Problems of the compressibility and creep of frozen ground in the complex stressed state are examined. Characteristics of creep of frozen skeletal and rocky fissured ground are highlighted, along with methods of evaluating their bulk strength. The results of experimental studies of the resistance of frozen ground under the ends of pile foundations are set forth. Methods of computing creep of frozen ground are proposed in the evaluation of the stability of underground excavations. The book is intended for designers, construction engineers, and mining engineers working in foundation-laying and sinking of underground excavations in long-frozen ground, and also for scientific workers concerned with the mechanics of frozen ground. (Author) Trans. of mono. Prochnost i Polzuchest Merzlykh Gruntov, Moscow, 1963 p1-219.